A randomised controlled trial of potential for pharmacologic prevention of new-onset albuminuria, hypertension and diabetes in a remote Aboriginal Australian community, 2008–2013 - Hoy, W.; Reid, Christopher; Huq, M.; McLeod, B.; Mott, S. (2019)
Introduction: We conducted a double-blind randomised controlled trial in a remote-living Australian Aboriginal group at high risk for chronic disease to assess whether pharmacological treatment with angiotensin converting enzyme inhibitor (ACEi) could delay the onset of albuminuria, hypertension or diabetes in people currently free of those conditions. Methods: Eligibility criteria in 2008 were age =18yr, blood pressure =140/90 mm/Hg, urinary albumin creatinine ratio (ACR) < 3.4 mg/mmol, normal levels of glycosylated haemoglobin, and, in females, infertility. A 2011 amendment allowed enrolment of fertile females using long-term contraception. “Treatment” was the ACEi perindopril arginine, or placebo, and participant events were ACR =3.4 mg/mmol and/or blood pressure >140/90 mm Hg and/or haemoglobin A1c >6.5%, and/or cardiovascular events. Results were analysed in 125 randomised participants who commenced treatment. Results: Recruitment was low, especially of women, and dropout rates high: there were finally 60 and 65 people in the ACEi and placebo groups respectively. In females, there were no events among 10 in the ACEi group, versus 5 events among 17 in the placebo group, and longitudinal ACR, HbA1c and blood pressure levels supported probable benefit of ACEi. There was no benefit of ACEi in males, but a probable benefit on diabetes/hypertension events. With the genders combined, there was probable reduction of diabetes (zero vs 4 events, p = 0.068), and of diabetes or hypertension (zero vs 5 events, p = 0.037). Discussion: In this high-risk population, ACEi probably delays development of albuminuria, diabetes and hypertension in females, and of non-ACR events overall. Repeat investigation with a larger sample size is warranted.